2019
DOI: 10.3390/su11236758
|View full text |Cite
|
Sign up to set email alerts
|

The Managerial Dimension of Open Data Success: Focusing on the Open Data Initiatives in Korean Local Governments

Abstract: Open government data (open data) initiatives have been at the forefront of the strategy to make more transparent, responsive, and accountable government, and thereby lead to open innovation across the public and private sector. Governments around the world often understand that open data is disclosing their data to the public as much as possible and that open data success is the result of a data and technology-related endeavor rather than the result of organizational, institutional, and environmental attribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…The 18th paper is about bridging the gap in the technology commercialization process by using a three-stage technology-product-market model, which is related to entrepreneurship leading culture for open innovation dynamics, in addition to marketing innovation and users' continuous intentions [134][135][136].…”
Section: Organizational Entrepreneurship Leading Culture For Open Innovation Dynamicsmentioning
confidence: 99%
“…The 18th paper is about bridging the gap in the technology commercialization process by using a three-stage technology-product-market model, which is related to entrepreneurship leading culture for open innovation dynamics, in addition to marketing innovation and users' continuous intentions [134][135][136].…”
Section: Organizational Entrepreneurship Leading Culture For Open Innovation Dynamicsmentioning
confidence: 99%
“…The third most utilized theory was DOI theory whereby it was employed by the four researchers [7,9,20,58]. The fourth theory, which was employed mostly, was resource-based theory and it was employed three times [6,11,37]. The remaining twenty-six (30) theories were employed only once whereas some of them were used combinedly.…”
Section: Geographical Distribution Of Articlesmentioning
confidence: 99%
“…Fourth, an SLR, a meta-analysis, and accordingly, the weight analysis may have a novel contribution and could bring in-depth insights to the OGD adoption studies from the perspective of public sector organizations which should then be rigorously tested in future. Fifth, there are several control variables introduced in earlier research, like institutional status of the chief information officer (CIO), institutionalization of informatization, financial size, financial independence, aging population, population density [37], department type [20], as well as moderating variables like power distance, uncertainty avoidance [11] are introduced. Further research should be carried out, including these control and moderating variables.…”
Section: Research Limitations and Future Research Directionsmentioning
confidence: 99%
“…As a result of the analysis, it was shown that the competency factors (individuals), cooperative factors, and policy factors had a significant effect on comprehensive performance. At the corporate level, the competency factors of individuals, cooperative factors, policy factors, and external environmental factors all had a significant effect [19]. Based on the data from the LINC project by the Ministry of Education in 2012, Kim Han-ki analyzed each influence factor by classifying the results of industry-academic cooperation as subordinate variables, such as objective performance and subjective performance [20].…”
Section: Literature Reviewmentioning
confidence: 99%